Prediction of heat and fluid flow in a heat exchanger tube mounted with V-cone bundles - Promthaisong, P.; Kumar, M.; Chuwattanakul, V.; Saysroy, A.; Eiamsa-ard, S. (Journal of Research and Applications in Mechanical Engineering, 2018)
A numerical prediction of turbulent forced convection is perfromed in order to gain an understanding of turbulence flow field, fluid temperature, local Nusselt number, pressure loss and thermal performance characteristics of a heat exchanger tubes mounted with V-cone bundles. V-cone is equipped at core of test tube and assumed as turbulator. The parameters for the investigation were considered at Reynolds number between 5000 and 15,000 and the distances between the V-cone pitch length to tube diameter were at P/D = 1.0, 2.0, 3.0 and 4.0. From the numerical result, it was found that the heat transfer enhancement increased with increasing Reynolds number and decreasing P/D, which the pressure loss was affected by P/D and Reynolds number, respectively. The thermal performances of the V-cones were also determined and compared with respect to heat transfer from the same tube without turbulators. The numerical results show that V-cone turbulators yield higher Nusselt number and friction factor than those the plain tube. For the V-cone turbulators, the thermal performance increases with increasing pitch ratio (PR) which the thermal performance was up to 1.01 at constant pumping power was archived.